HAK PERLINDUNGAN SOSIAL BAGI LANJUT USIA DI KECAMATAN MEDAN AMPLAS MENURUT UU NO. 13 TAHUN 1998 DAN HUKUM ISLAM - Pagar, Hafsah, Uswatun Hasanah (UIN SU, 2018)
The studies about âThe Rights of Social Protection for Aged in Medan Amplas based on Law No. 13 of 1998 and Islamic Lawâ. The study will investigate of how is the implementation of the rights of social protection for aged in Medan Amplas based on Law No. 13 of 1998, how is the implementation of the rights of social protection for aged in Medan Amplas based on Islamic Law and what is the problem and solution in implementing the social protection for aged in Medan Amplas.The findings showed that the rights of social protection for aged in Medan Amplas did not fulfill properly. It was based on the information which had been got from the Social Services of Medan and also the observation and interview which had been done. They were the rights in getting ASLUT (The social assistance for Aged) and PKH (The Prospects of Family Program). Most of aged did not get those kinds of aid. Moreover, there were only 175 aged who got the ASLUT in Medan. The information had been found that the limitation of fund from the government caused the rights for most aged didnât fulfill well. The case can be the good input for government to increase the fund for the aged to fulfill their rights of social protection.